Musculus extensor digitorum brevis in dog - İsmail Türkmenoğlu (Eurasian Journal of Veterinary Sciences)
In this Study, musculus extensor digitorum brevis forming variation in dog was examined. Twelve dogs of different age, weight and sex were used for the study. Musculus extensor digitorum brevis originates from Ihe cranial and distal part of the calcaneus. It consist of the three heads. Of the three terminal tendons, the medial, intermediate and lateral ones were observed to go to the phalanx proximalis of digit II, digits III and IV. phalanx media of digit IV respectively. In a case, the tendon of caput mediale was determined to terminate in Ihe phalanx proximalis of digits II and III.